Assessment and Evaluation of the Intake of Sugars in European Countries - Michiel R. H. Löwik (Applied Sciences, 2021)
The intake of sugars is a trending topic in nutrition and health. For an evaluation of the sugar intake (comparison with existing guidelines), up-to-date information on the guidelines, dietary intake and trends in the intake is needed. The available information for European countries is presented in this review. The existing guidelines on the intake show that there is currently no consensus among the experts from different organizations. The differences are mainly due to the selection of the adverse health outcomes for which there is sufficient evidence. Data from national European surveys show that the mean proportion of energy coming from added sugars for most European population groups is below 10%, and that the trend in the intake seems to be downwards. There are, however, many serious uncertainties and assumptions needed for the assessment of the intake of sugars. For instance, the assessment reflects a short period of the lives of the respondents, the data collection in several surveys was conducted more than 10 years ago, and recent reformulations of the industry are not considered in the food composition tables. Due to the uncertainties regarding the assessment of the sugar intake in Europe, the information should be used prudently and with care.